Determination of Local People Consensus in the Use Of Medicinal Plants of Thakurgaon District (Bangladesh Journal of Plant Taxonomy, 2022)
Consensus in the use of medicinal plants is one of the criteria to find the potential medicinal plants for further in-depth investigation. The present study was conducted with the aim to determine the people consensus in the use of medicinal plants in Thakurgaon district. Data of medicinal plants were recorded using key informant interviews, semi structured interviews and group discussion. A total of 102 medicinal plant species under 49 families with 185 formularies to treat 54 ailments were recorded from the study area. The most frequently utilized plant species are trees (38%) followed by herbs (34%), shrubs (18%) and climbers (10%). The major part used for medicines was leaf. Oral consumption was the main mode of treatment in the study area followed by external application. The top Fic value was obtained in case of heart diseases (0.92). The most cited species used to treat this ailment was Allium sativum, Phyllanthus emblica, Spondias pinnata and Terminalia arjuna. The second highest Fic value was found in respiratory disorders (0.89) followed by cuts and wounds (0.85), skin diseases (0.84) and gastrointestinal disorders (0.81). In case of Fl value, Allium sativum, Spondias pinnata, Cynodon dactylon, Lawsonia inermis, Zingiber officinale, Saccharum officinarum, Tagetes erecta and Baccaurea ramiflora were showed 100%. The species of higher citation frequency were Allium sativum, Phyllanthus emblica, Spondias pinnata, Terminalia arjuna, Cynodon dactylon and Ocimum sanctum. This study recommends that the species which showed high Fic, Fl, Cf values could be used for further phytochemical analysis to investigate active compounds for the discovery of new drugs from medicinal plants.Bangladesh J. Plant Taxon. 29(2): 345-360, 2022 (December)